Transstomal Small Bowel Evisceration after Colonic Perforation Secondary to Ischemic Colitis. (17th September 2012) - Guner, Ali; Kahraman, Izzettin; Ozkan, Omer Faruk; Aktas, Adem; Kece, Can
Abstract : Intestinal stomas are commonly used in a temporary or permanent fashion in gastrointestinal surgeries. The complication rate of stomas has been reported to vary between 23 and 50%. There is only one case in the literature involving transstomal small bowel evisceration following colonic perforation. In this paper, we aimed to present a patient with a perforated colon secondary to ischemic colitis, which resulted in small bowel evisceration through this perforation site.